A Comparative Analysis of QRIS and Debit Card Usage in Generation Z’s Cashless Transactions in Banjarmasin - Noor Lisa; Erissa Nilasari; Ilham Akbar; Faqih El Wafa; Jumiatul Akbari (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2026)
The rapid digital transformation has fundamentally shifted consumer behavior toward cashless payment systems. While digital payment adoption among digital natives is widely acknowledged, limited research directly compares agile mobile platforms with conventional banking instruments. Consequently, this study aims to empirically compare the usage of the Quick Response Code Indonesian Standard (QRIS) and debit cards in Generation Z’s daily cashless transactions within Banjarmasin City. Employing a quantitative comparative approach, primary data were collected through structured online questionnaires from a purposive sample of 100 Generation Z respondents. The gathered data were then statistically analyzed utilizing the non-parametric Mann-Whitney test. The analysis reveals a significant disparity in usage preferences, demonstrating that QRIS decisively outperforms debit cards. Generation Z strongly favors QRIS for its mobility, cost-effectiveness, and superior transaction speed. Conversely, debit card usage is increasingly constrained by its reliance on physical infrastructure, such as EDC machines. The study concludes that mobile-based digital payments are rapidly displacing traditional card instruments. However, this study is limited because it evaluates only two specific payment methods within a single demographic in a single regional city, suggesting the need for broader future research.